Evaluation of the effect of the herpes zoster vaccination programme 3 years after its introduction in England: a population-based study. (February 2018) - Amirthalingam, Gayatri; Andrews, Nick; Keel, Philip; Mullett, David; Correa, Ana; de Lusignan, Simon; Ramsay, Mary
Summary: Background: In 2013, a herpes zoster vaccination programme was introduced in England for adults aged 70 years with a phased catch-up programme for those aged 71–79 years. We aimed to evaluate the effect of the first 3 years of the vaccination programme on incidence of herpes zoster and postherpetic neuralgia in this population. Methods: In this population-based study, we extracted data from the Royal College of General Practitioners sentinel primary care network on consultations with patients aged 60–89 years for herpes zoster and postherpetic neuralgia occurring between Oct 1, 2005, and Sept 30, 2016, obtaining data from 164 practices. We identified individual data on herpes zoster vaccinations administered and consultations for herpes zoster and postherpetic neuralgia, and aggregated these data to estimate vaccine coverage and incidence of herpes zoster and postherpetic neuralgia consultations. We defined age cohorts to identify participants targeted in each year of the programme, and as part of the routine or catch-up programme. We modelled incidence according to age, region, gender, time period, and vaccine eligibility using multivariable Poisson regression with an offset for person-years. Findings: Our analysis included 3·36 million person-years of data, corresponding to an average of 310 001 patients aged 60–89 years who were registered at an RCGP practice each year. By Aug 31, 2016, uptake of the vaccine varied between 58% for the recently targeted cohorts and 72% for the first routine cohort. Across the first 3 years of vaccination for the three routine cohorts, incidence of herpes zoster fell by 35% (incidence rate ratio 0·65 [95% 0·60–0·72]) and of postherpetic neuralgia fell by 50% (0·50 [0·38–0·67]). The equivalent reduction for the four catch-up cohorts was 33% for herpes zoster (incidence rate ratio 0·67 [0·61–0·74]) and 38% for postherpetic neuralgia (0·62 [0·50–0·79]). These reductions are consistent with a vaccine effectiveness of about 62% against herpes zoster and 70–88% against postherpetic neuralgia. Interpretation: The herpes zoster vaccination programme in England has had a population impact equivalent to about 17 000 fewer episodes of herpes zoster and 3300 fewer episodes of postherpetic neuralgia among 5·5 million eligible individuals in the first 3 years of the programme. Communication of the public health impact of this programme will be important to reverse the recent trend of declining vaccine coverage. Funding: Public Health England.